Investigating the feasibility of using carbon fiber tapes as reinforcement for 3D concrete printing. Issue 4 (5th August 2021) - Scheurer, Martin; Quenzel, Philipp; Nölke, Peter; Reuter‐Schniete, Jonas; Gries, Thomas
Abstract: The main advantages of textiles as concrete reinforcement are high corrosion resistance, allowing for thin concrete covers, high drapability, and high strength. Due to these advantages, textiles are particularly suitable as reinforcement for 3D printed concrete, where thin elements and freeform geometries are possible. In this article, a new type of textile reinforcement for the integration into 3D concrete printing is investigated: unidirectional carbon fiber tapes. Carbon fiber tapes are made from carbon fiber rovings by spreading. Three carbon fiber tapes are produced and used as reinforcement in concrete specimens subjected to four‐point bending tests. The results show that for a spreading factor of 2.2 (areal weight 136 g/m 2 ), the flexural strength of the beams is increased by 125% compared to reference beams reinforced with unspread rovings. Further increase of the spreading factor does not increase flexural strength further as the failure mode changes from rupture to spalling.